Mutual funds and unit trust : the Trinidad and Tobago experience - Swan-Daniel, Sandra ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Gives an account of the origins of the mutual fund industry in Trinidad & Tobago and examines the degree to which the industry has been successful in the mobilisation of domestic savings. Explores the need for pending charges in the regulation and supervisory framework of the mutual fund industry.